Prevalence of Microalbuminuria in Non-diabetic Hypertensive Patients and its Correlation with Changes in Left Ventricular and Left Atrial Characteristics - Bhusal, Khema Raj; Devkota, Surya; Pathak, Surya; Khanal, Pratik; Khanal, Umesh; Thapalia, Poojan; Neupane, Srijana; Gyanwali , Pradip; Simkhada, Rabindra; Oli, Krishna Kumar (Journal of Nepal Health Research Council, 2023)
Background: Microalbuminuria is urinary albumin excretion in the range of 30-300 mg per 24 hours and is considered as an abnormal albumin excretion rate. Microalbuminuria is associated with epithelial dysfunction and have a high risk for target organ damage resulting in stroke, retinopathy and adverse cardiovascular events. The objective of the study was to determine the prevalence of microalbuminuria in non-diabetic hypertensive patients and its correlation with cardiovascular changes. Methods: A quantitative cross-sectional study was done in 107 participants diagnosed as non-diabetic hypertensive patients visiting to Manmohan Memorial medical college and Teaching hospital and Manmohan Cardio-thoracic Vascular and transplant Centre. The assessed parameters were basic metabolic profile, urine evaluation and Echocardiography. Results:The results showed microalbuminuria in 28 study participants and not seen in 79 participants. Similarly, microalbuminuria was observed more comparable in those with presence of left ventricular hypertrophy as compared to the absence of left ventricular hypertrophy (29.3% versus 22.8%) (p value 0.469); those with presence of left ventricular diastolic dysfunction as compared to the absence of left ventricular diastolic dysfunction (31.1% versus 19%) (p value 0.170) and those with dilated left atrium as compared to normal left atrium (26.7% versus 23.9%) (p value 0.820). In case of left ventricular ejection fraction, those with normal left ventricular ejection fraction (26.3%) had slightly higher proportion of micro-albuminuria than those with mild to moderate left ventricular systolic dysfunction (20%) (p value= 0.755) Conclusions: There was no significant difference in the level of micro-albuminuria between non-diabetics, hypertensive patients with cardio vascular changes compared to patients with no cardiovascular changes. Keywords: Hypertension; microalbuminuria; non-diabetic